Understanding how social norms influence access to and utilization of adolescent sexual and reproductive health services in Northern Nigeria - Taiwo, Modupe Oladunni; Oyekenu, Oluwatoyin; Hussaini, Rahinatu (Frontiers in Sociology, 2023)
This study explored the influence of social norms on the access and utilization of sexual and reproductive health services by adolescents. Apart from individual and environmental barriers, social norms influence contraceptive decisions and ultimately sexual and reproductive health outcomes. Social norms which shape group behaviour describes acceptable standards of behaviour and evokes sanctions when such behavior standards are not adhered. Sexually active adolescents in Nigeria have a relatively low level of modern contraceptive use being influenced by social norms. Scale-up of adolescent reproductive health intervention that integrates normative change for a wider impact of programs remains challenging